2018
DOI: 10.1038/s41598-018-19599-1
|View full text |Cite
|
Sign up to set email alerts
|

v-Src-driven transformation is due to chromosome abnormalities but not Src-mediated growth signaling

Abstract: v-Src is the first identified oncogene product and has a strong tyrosine kinase activity. Much of the literature indicates that v-Src expression induces anchorage-independent and infinite cell proliferation through continuous stimulation of growth signaling by v-Src activity. Although all of v-Src-expressing cells are supposed to form transformed colonies, low frequencies of v-Src-induced colony formation have been observed so far. Using cells that exhibit high expression efficiencies of inducible v-Src, we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The chromosome instability generates genetic diversity, and cells capable of adapting to growth-suppressive conditions by anti-cancer drugs or cells gaining metastatic ability can be selected (7). Indeed, we recently reported that v-Src-driven transformation is attributable to chromosomal abnormalities (45). It is noteworthy that Csk knockdown can induce mitotic slippage, similar to v-Src expression, suggesting that increased Src kinase activity can attenuate SAC and cause mitotic slippage.…”
Section: V-src Induces Mitotic Slippage Through Cdk1 Phosphorylationmentioning
confidence: 99%
“…The chromosome instability generates genetic diversity, and cells capable of adapting to growth-suppressive conditions by anti-cancer drugs or cells gaining metastatic ability can be selected (7). Indeed, we recently reported that v-Src-driven transformation is attributable to chromosomal abnormalities (45). It is noteworthy that Csk knockdown can induce mitotic slippage, similar to v-Src expression, suggesting that increased Src kinase activity can attenuate SAC and cause mitotic slippage.…”
Section: V-src Induces Mitotic Slippage Through Cdk1 Phosphorylationmentioning
confidence: 99%
“…HeLa S3/TR cells inducibly expressing Fyn (HeLa S3/TR/Fyn) were generated using HeLa S3/TR cells, which constitutively express the tetracycline repressor (TR) 24 , and pcDNA4/TO/neo/Fyn, as previously described 22 . Strictly controlled inducible expression is advantageous because protein expression levels may be adjusted to an appropriate amount 24 , 26 . SFK-mediated tyrosine phosphorylation was assessed using 20 µM PP2 (Sigma-Aldrich), 10 µM SU6656, 0.6 µM MLN8237 (Selleck Chemicals), and 10 µM sunitinib (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…(i) (G 1 /S phase) Cells were cultured for 20–24 h with 4 mM thymidine (thymidine block) 55 . Alternatively, cells were cultured with 4 mM thymidine for 20 h, transferred into fresh medium for 9 h, and then cultured with 4 mM thymidine (double thymidine block) for 15 h 26 . (ii) (Late G 2 phase) Cells arrested in the G 1 /S phase by the thymidine block were released for 9 h, and then treated with 9 μM of the Cdk1 inhibitor RO-3306 for 4–9 h 22 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…v‐Src promotes cell growth signals such as activation of MAPK/ERK pathway and CDK‐cyclin complexes. However, we showed that the inducible expression of v‐Src inhibits cell proliferation along with up‐regulation of the CDK inhibitor p21 7,8 . Given that v‐Src causes mitotic defects such as chromosome bridge formation and brings about colony formation at a low frequency, v‐Src‐mediated cell transformation may be attributed to stochastic results of chromosomal abnormalities 7‐9 .…”
Section: Introductionmentioning
confidence: 93%